Changes in the Barents Sea fish community induced by environmental change and fishery - Aschan, Michaela; Fossheim, Maria; Primicerio, Raul (ICES, 2009)
A spatio-temporal analysis of Barents Sea survey data from the deeper parts of the Barents Sea shows a sudden change in fish community structure and abundance taking place in the mid 1980s and 1990s. The change in fish community structure is concomitant with climatic change and increasing fishing effort. Fishery may amplify the effects of climate forcing, and oppose recovery from the impact of climatic events. To characterize the effects of climate and fishery, survey trawl data, temperature data and log book data from the shrimp fishery are analyzed for the period 1980-2007. The climate regime shifts in the mid 80s and 90s with decline in North Atlantic Oscillation and temperature resulted in abrupt decline in fish abundance, decline in biodiversity and increase in pelagic demersal ratio. The shrimp stock also declined and the response of the shrimp industry was a reduction in effort. As the standardised fishing effort is our only measure of fishing impact it becomes difficult to separate between the two impact factors temperature and fisheries. Yet, preliminary results indicate that the shrimp fishery has minor influence on the fish community. The fish community in the Barents Sea has changed into a more North Sea like pelagic-dominated ecosystem. The sudden changes in abundance and diversity reveal that the Barents Sea fish community is sensitive to environmental change. High precaution is needed in the management of all human activities in the Barents Sea due to its low species diversity and resilience. Keywords: Barents Sea, climate change, fish community, fisheries